The influence of price levels, product quality and service quality on the purchasing decisions of customers of the SA Interior store at ITC Cempaka Mas - Brastoro Brastoro; Muhammad Fuad; Elisabeth Vita; Elis Sondang Dasawaty; Abhishek Pursnani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Interior Design of a room is the main aspect that contributes to the beauty of the room and also the comfort of people in the room. Globalization contributes to the rampant development of sales of products for interior design needs with a supply of quality goods and competitive prices. Many new entrepreneurs act as part of the distribution channel and open retail businesses. One of them is SA Interior. The theories used in this study are price, product quality, service quality and purchasing decisions. Price Level, Product Quality and Quality of Service are free/independent variables (X), Purchasing Decisions are bound/dependent variables (Y) and the object of research is the SA Interior store at ITC Cempaka Mas. The sample used in this study was SA Interior customers who purchased SA Interior products at least 1 time. The data collection technique uses communication techniques by distributing questionnaires (via Google Form) with a total of 100 respondents. This research shows that the price level has a positive and significant influence on the purchasing decisions of SA Interior customers, the quality of the products has a positive and significant influence on the purchasing decisions of SA Interior customers and the quality of service has a positive and significant influence on the purchasing decisions of SA Interior customers. Simultaneous price levels, product quality and service quality have a significant influence on the purchasing decisions of SA Interior customers. The conclusion of this study is that the price level, product quality and service quality have a positive and significant influence on the purchasing decisions of SA Interior customers at ITC Cempaka Mas.